Conformal Vector Fields on Doubly Warped Product Manifolds and Applications - H. K. El-Sayied; Sameh Shenawy; Noha Syied (Advances in Mathematical Physics)
This article aimed to study and explore conformal vector fields on doubly warped product manifolds as well as on doubly warped spacetime. Then we derive sufficient conditions for matter and Ricci collineations on doubly warped product manifolds. A special attention is paid to concurrent vector fields. Finally, Ricci solitons on doubly warped product spacetime admitting conformal vector fields are considered.